Assessing intercultural competence using videotapes: A comparison study of home students' performance - Zhaoming Wang (Peoples' Friendship University of Russia (RUDN University), 2022)
How to assess intercultural competence is the key to exploring intercultural effectiveness. Although various methods have been developed for assessing intercultural competence (e.g., interviews, self-report questionnaire, critical analysis, etc.), this study assesses intercultural competence using videotapes to observe participants' performance in the multicultural interactions. A comparative study was conducted comparing home students who were interculturally trained and who did not. By examining their performance in group discussion, two specific aspects - eye gaze and amount of talk - were analysed by both quantitative and qualitative techniques. The results show that trained home students not only had more and longer eye gazes than the untrained students during group discussion, but they also used more other-oriented speech than the untrained. Such findings indicate that the trained home students were more interculturally competent than the untrained especially in the multicultural intra-group interaction setting. As there are many other variables to examine (e.g., non-verbal cues such as body gestures and facial expressions), this study demonstrates a way to assess intercultural competence using videotapes in both verbal and non-verbal cues for the future research.